Armrests and back support reduced biomechanical loading in the neck and upper extremities during mobile phone use. (November 2018) - Syamala, Kartheek Reddy; Ailneni, Ravi Charan; Kim, Jeong Ho; Hwang, Jaejin
Abstract: Mobile phone use is known to be associated with musculoskeletal pain in the neck and upper extremities because of related physical risk factors, including awkward postures. A chair that provides adequate support (armrests and back support) may reduce biomechanical loading in the neck and shoulder regions. Therefore, we conducted a repeated-measures laboratory study with 20 participants (23 ± 1.9 years; 10 males) to determine whether armrests and back support during mobile phone use reduced head/neck flexion, gravitational moment, and muscle activity in the neck and shoulder regions. The results showed that the chair support (armrests and back support) reduced head/neck flexion ( p < 0.001), gravitational moment ( p < 0.001), and muscle activity ( p < 0.01) in the neck and shoulder regions significantly compared to no chair support. These results indicate that a chair with adequate support can be an effective intervention to reduce the biomechanical exposures and associated muscular pain in the neck and shoulders during mobile phone use. Highlights: Effects of chair supports on reducing physical stresses during texting was tested. Chair supports reduced the flexion, moment, and muscle activity of neck and shoulders. Placing the phone at eye level with chair supports showed the lowest physical stress.